Virtual exhibition: journey of Professor Dr. Abd Halim Mohd Noor / Perpustakaan Tun Abdul Razak UiTM Cawangan Melaka - UiTM Cawangan Melaka, Perpustakaan Tun Abdul Razak (Perpustakaan Tun Abdul Razak, UiTM Cawangan Melaka, 2023)
Archives Unit, Tun Abdul Razak Library UiTM Melaka Branch has become a Committee Member for exhibition in conjunction with the program "UiTM Melaka Knowledge Sharing Session Series 1: Top Level Management Leadership". The Archives Unit has conducted an exhibition titled "Journey of Professor Dr. Abd Halim Mohd Noor". This exhibition is seen to be very significant with the main objective of cultivating knowledge, consolidating knowledge and leadership management among staff of UiTM Melaka Branch. In addition, able to promote the services of the Archives Unit in supporting efforts to raise awareness to all UiTM Citizens about the importance of University Records Management that all UiTM citizens must know to preserve the history of UiTM. This virtual exhibition can be accessed at PTAR UiTM Melaka Branch website in the Virtual Exhibition section.